Capital Expenditure, Kesempatan Bertumbuh, Volatilitas Arus Kas dan Cash Holding - Shari, Putu Nadya; Badera, I Nyoman Dewa (E-Jurnal Akuntansi; Vol 33 No 6 (2023)DO - 10.24843/EJA.2023.v33.i06.p07, 2023)
Cash holding or the availability of cash is very important in a company so that the company must have a good cash management system, especially companies that are vulnerable to a liquidity crisis. This study aims to empirically examine the effect of capital expenditure, growth opportunities, and cash flow volatility on cash holdings. The research was conducted on property and real estate companies listed on the Indonesia Stock Exchange with a total sample of 30 companies. The analysis technique used is multiple linear regression analysis. The results showed that capital expenditure had a significant negative effect, growth opportunities did not have a significant effect, and cash flow volatility had a significant positive effect. The results of the study contribute to confirming the trade-off theory and the pecking order theory as well as providing an empirical picture of the effect of capital expenditure, growth opportunities, and cash flow volatility on the cash holdings of companies in the property and real estate sector. Keywords: Cash Holding, Capital Expenditure, Growth Opportunity, Cash Flow Volatility.